استخدام الشبكات العصبية الصنعية مع تقنية التحويل المويجي للتنبؤ بالتدفق اليومي الوارد إلى بحيرة سد 16 تشرين - غطفان عمار; بادية حيدر (Tishreen University, 2018)
يُعدُّ تقييم موارد المياه السطحية من المدخلات الضرورية لحل قضايا إدارة المياه، والتي تتضمن إيجاد علاقة بين الأمطار والجريانات السطحية، وتعتبر هذه العلاقة على درجة عالية من التعقيد، حيث أن الأمطار من أهم العوامل التي تؤثر بشكل كبير على جريان الأنهار، وعملية التنبؤ بهذه الجريانات يجب أن تأخذ هذا العامل بعين الاعتبار، وبكثير من الاهتمام والدراسة، وتعتبر الشبكات العصبية الصنعية من أهم الطرائق الحديثة من حيث دقة نتائجها في الربط بين هذه العوامل المتعددة والبالغة التعقيد. ومن أجل التنبؤ بالجريان اليومي الوارد إلى بحيرة سد 16 تشرين في اللاذقية، موضوع بحثنا، تم تطبيق نماذج مختلفة من الشبكات العصبية الصنعية (ANN)، كانت مدخلاتها تدفقات سابقة للأمطار والجريانات. قسمت مجموعة البيانات للفترة الممتدة بين عامي (2006-2012) إلى مجموعتين: تدريب واختبار، وقد تم معالجة البيانات قبل إدخالها إلى الشبكة العصبية باستخدام تقنية تحويل المويجات المتقطع، للتخلص من مشاكل القيم العظمى والقيم الصفرية، حيث حللت السلاسل الزمنية إلى ثلاثة مستويات من الدقة واستخدمت السلاسل الفرعية الناتجة كمدخلات للشبكة العصبية أمامية التغذية التي تعتمد على خوارزمية الانتشار العكسي لتدريبها. أشارت النتائج إلى أن الشبكة العصبية ذات الهيكلية )1-2-6) نموذج Wavelet-ANN، هي الأفضل في تمثيل الظاهرة المدروسة والأقدر على التنبؤ بالجريان اليومي الوارد إلى بحيرة سد 16 تشرين ليوم واحد قادم، حيث بلغ معامل الارتباط وجذر مربع متوسط الخطأ (R2=0.96، RMSE=1.97m3/sec)، على الترتيب. The evaluation of surface water resources is a necessary input to solving water management problems, which includes finding a relationship between precipitation and runoff, and this relationship is a high degree of complexity. The rain of the most important factors that greatly effect on rivers discharge, and process to prediction of these flows must take this factor into account, and much of the attention and study, artificial neural networks and is considered one of the most modern methods in terms of accuracy results in linking these multiple factors and highly complex. In order to predict the runoff contained daily to Lake Dam Tishreen 16 in Latakia, the subject of our research, the application of different models of artificial neural networks (ANN), was the previous input flows and rain. Divided the data set for the period between (2006-2012) into two sets: training and test, has been processing the data before using them as inputs to the neural network using Discrete Wavelet Transform technique, to get rid of the maximum values and the values of zero, where t the analysis of time series at three levels of accuracy before they are used sub- series resulting as inputs to the Feed Forward ANN that depend back-propagation algorithm for training. The results indicated that with the structural neural network (1-2-6) Wavelet-ANN model, are the best in the representation of the characteristics studied and best able to predict runoff daily contained to Lake Dam Tishreen 16 for a day in advance, where he reached the correlation coefficient the root of the mean of squared-errors (R2 = 0.96, RMSE = 1.97m3 / sec), respectively.